Penerapan Gamifikasi dalam Pembelajaran Konjungsi Teks Deskripsi Kelas 9I SMPN 13 Surabaya - Hanikmah Rahmadani; Sueb Hadi; Inna Prabandari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research examines the use of gamification in learning descriptive text conjunctions for class 9I of SMP Negeri 13 Surabaya. How the use of gamification in learning can improve the results and motivation of learning Indonesian for class 9I students. The aim of this research is (1) to increase the learning activities of class 9I students at SMP Negeri 13 Surabaya through the application of gamification in learning (2) to improve the learning outcomes of descriptive text conjunctions for class 9I students at SMP Negeri 13 Surabaya. This research is Classroom Action Research (PTK) which includes planning, implementation, observation and reflection. Data collection methods use questionnaires and observation. The instrument used is quantitative descriptive data analysis. The results of this research show an increase in students' motivation and learning participation, as well as a better understanding of conjunctions in Indonesian descriptive texts.